Sensitivity of Coal Reserve Economic Feasibility to Price Fluctuations: A Case Study of an Open-Pit Coal Mine in East Kalimantan, Indonesia - Arif Deswanda Cismawan; Eddy Ibrahim; Eddy Sutriyono; M. Taufik Toha; Maulana Yusuf; Rahmat Wahyudi Putra (International Journal of Engineering Continuity, 2026)
Coal price volatility is one of the most important factors affecting the economic feasibility of mining operations, particularly marginal coal reserves that are highly sensitive to changes in cost and revenue. This study evaluates the economic feasibility of marginal coal reserves under different coal price scenarios using a case study from an open-pit coal mine in East Kalimantan, Indonesia. The analysis applies a simplified discounted cash flow framework combined with operating margin analysis, critical price determination, and price sensitivity assessment. The results show that, at a base coal price of USD 43,97/ton, the project remains economically feasible, with an operating margin of USD 6,05/ton and a net present value of USD 82,91 million. However, a 20% decline in coal price results in a negative margin of USD 2,74/ton, making the project no longer economically feasible. The critical price was identified at USD 37,92/ton, representing the break-even threshold. The sensitivity analysis further demonstrates that the economic status of marginal coal reserves is dynamic and can shift from feasible to marginal or not feasible depending on market conditions. These findings highlight the importance of integrating price sensitivity into reserve evaluation and mine planning. The proposed framework provides a practical decision-support approach for reserve classification, production planning, and resource optimization under uncertain economic conditions. The main contribution of this study is the development of a practical techno-economic classification framework that links coal price variation with reserve feasibility status through the integration of critical price, operating margin, and break-even stripping ratio. This framework allows marginal reserves to be evaluated as dynamic economic entities rather than as fixed reserve categories under a single base-case price assumption.